Specific Language Impairment with or without ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
A neuropsychological study of the association between specific language impairment (SLI) and hyperactivity was conducted on four groups of 6-year-old children (5 boys and 5 girls in each group) at the Department of Psychiatry, University of Cambridge, UK.